1997
DOI: 10.1243/0957650971537178
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on flow and heat transfer in large-scale, turbine cooling, representative, rib-roughened channels

Abstract: This paper deals with the application of a three-dimensional Navier-Stokes solver for the prediction of steady viscous compressible flow and heat transfer in a square channel with one rib-roughened wall. The computation results are compared with detailed experiments carried out at the von Karman Institute. The two-dimensional computations agree rather well with the experiments for the prediction of the aerodynamics, even if the recirculation length is overestimated. In this case, a k-l turbulence model seems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The accurate prediction of these two curves is difficult to achieve because of the recirculation of flow near the ribs and the localized secondary flow effect. Many computational studies have attempted to correctly predict this smooth wall heat transfer effect using different turbulence models with little success (Ooi et al, 2002;Arts et al, 1997;Saidi and Sundén, 2001;Sleiti and Kapat, 2004). In the 180°bend region, a mass transfer experiment by showed results for a channel with geometry similar to that of the present study (e/D h = 0.094, P/ e = 10) with a Reynolds number of 30,000.…”
Section: Heat Transfer Augmentationmentioning
confidence: 53%
See 2 more Smart Citations
“…The accurate prediction of these two curves is difficult to achieve because of the recirculation of flow near the ribs and the localized secondary flow effect. Many computational studies have attempted to correctly predict this smooth wall heat transfer effect using different turbulence models with little success (Ooi et al, 2002;Arts et al, 1997;Saidi and Sundén, 2001;Sleiti and Kapat, 2004). In the 180°bend region, a mass transfer experiment by showed results for a channel with geometry similar to that of the present study (e/D h = 0.094, P/ e = 10) with a Reynolds number of 30,000.…”
Section: Heat Transfer Augmentationmentioning
confidence: 53%
“…Two two-dimensional calculations by Liou et al (1992Liou et al ( , 1993b) used a k-e-A model, which is a standard k-e model coupled with an Algebraic Stress Model (ASM), and were able to account for the anisotropy of turbulence. Calculations using a number of different turbulence models by Arts et al (1997) showed that a three dimensional k-l model (similar to k-e) was not sufficient in predicting the secondary flows and an ASM was required. A comparison between an eddy-viscosity model (EVM) and an ASM reported that the average heat transfer on the side wall (which is most affected by secondary flows) was predicted to within 5%, but contours of the regions showed predictions that were completely different from what the experimental measurements showed (Saidi and Sundén, 2001).…”
Section: Review Of Relevant Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of rib turbulators have been investigated by many researchers; in particular the work of Ekkad and Han,6 Ekkad et al ,7 Park et al ,8 Akella and Han,9 and Arts et al 10 are acknowledged. The present tests dealt with a square channel, 80 mm side length, 2,000 mm long, which was tested both with and without ribs.…”
Section: Resultsmentioning
confidence: 99%
“…T. Arts et al combined experimental and 2D numerical methods to investigate heat transfer in rib-roughened channels. [9] J. E. Dees, D. G. Bogard., performed experimental and computational investigation to study a cooling channel with 90-degree ribs in 2012.…”
Section: Introductionmentioning
confidence: 99%